Negative returns: U.S. military policy and anti-american terrorism - Eugen Dimant; Tim Krieger; Daniel Meierrieks (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2017)
We investigate the effect of U.S. military aid and U.S. troop deployments on anti-American terrorism, using a sample of 106 countries between 1986 and 2011. We find that greater military commitment leads to more anti-American terrorism. We study the underlying mechanisms using a mediation analysis and show that both U.S. military aid and troop deployments in foreign countries do not improve local state capacity. Rather, we find that more military aid (but not troop deployments) is linked to poorer political-institutional outcomes in aid-receiving countries, explaining the positive association between U.S. military aid and anti-American terrorism. Our findings suggest that U.S. military policy does not make the United States safer from transnational terrorism.
Keywords: D74; F35; F50; 330; oil rents; inequality; VAR; ARDL; sanctions; Iran